Using Software Containers for Privileged Access Management in Cloud Environments: A Novel Approach to Handle Access Management for Cloud-based Networks - Steinhoff, Marleen (Nordic and Baltic Journal of Information & Communications Technologies, 2021)
This paper presents a novel approach for privileged access and session management using containers. Current solutions are built using proxies, proxy suites or jump servers, but they do not cater for third party remote access security requirements, have additional vulnerabilities and have scalabilty limitations. The novelty of the solution proposed in this paper is a global orchestrator that instantiates a purpose-built container adapted to the virtual network functions’ system. Every container has a logging function, a pre-defined time-to-live and one-time-credentials. This approach is secure because the containers isolate different connections, privileges are restricted, permissions are always time-limited and the provider has full control over the sessions. The solution brings several other security enhancements, discussed in this paper.